Augmentative alternative communication for speech delay children with gamifications / Nora Yanti Che Jan, Nor Kamaliah Mohd Kamaruddin and Mahfudzah Othman - Che Jan, Nora Yanti; Mohd Kamaruddin, Nor Kamaliah; Othman, Mahfudzah (UiTM Cawangan Perlis, 2021)
This paper discusses the development of an aided augmentative alternative communication (AAC) web based system to assist speech delayed children between the age of four to nine years old that incorporates the gamifications techniques. The aim is to provide a set of strategies and techniques that can be used to support communications for children with communication needs. The research methodology used to develop the AAC web-based system with gamifications start with the preliminary investigation, proposing the framework of the prototype system that consists of two main modules, which are the speech recognition and spell session modules, design and development of the system and usability evaluation. The results of the usability testing that has been conducted to thirty speech delayed children showed that the ACC webbased system with gamifications have been proven satisfactory to support and assist speech delayed children in improving their speech and language learning.